2020
DOI: 10.3389/fonc.2020.01245
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed Pseudogene HLA-DPB2 Promotes Tumor Immune Infiltrates by Regulating HLA-DPB1 and Indicates a Better Prognosis in Breast Cancer

Abstract: Immune checkpoint inhibitors (ICIs) have been successfully used for treating melanoma and non-small cell lung cancer. However, many patients with breast cancer (BC) show low response to ICIs due to the paucity of infiltrating immune cells. Pseudogenes, as a particular kind of long-chain noncoding RNA, play vital roles in tumorigenesis, but their potential roles in tumor immunology remain unclear. In this study that used data from online databases, the novel pseudogene HLA-DPB2 and its pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 65 publications
1
33
0
Order By: Relevance
“…Hou et al ( 44 ) reported that miR-370-3p expression was increased in cerebral aneurysm tissues compared with normal tissues, and miR-370-3p was involved in the development of cerebral aneurysm by targeting the KDR/AKT signaling pathway. Lyu et al ( 45 ) suggested that miR-370-3p, as a core molecular, played important role in breast cancer. The pseudogene HLA-DPB2 upregulated HLA-DPB1 through sponging miR-370-3p to exert antitumor effect by recruiting tumor-infiltrating immune cells into the breast tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Hou et al ( 44 ) reported that miR-370-3p expression was increased in cerebral aneurysm tissues compared with normal tissues, and miR-370-3p was involved in the development of cerebral aneurysm by targeting the KDR/AKT signaling pathway. Lyu et al ( 45 ) suggested that miR-370-3p, as a core molecular, played important role in breast cancer. The pseudogene HLA-DPB2 upregulated HLA-DPB1 through sponging miR-370-3p to exert antitumor effect by recruiting tumor-infiltrating immune cells into the breast tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed that tumor immune cell infiltration could influence the efficacies of chemotherapy, radiotherapy, or immunotherapy and prognosis of cancer patients. [35][36][37] Our work suggested that SEMA3F was significantly positively correlated with various immune cells, including B cell, CD8 + T cell, CD4 + T cell, macrophage, neutrophil, and dendritic cell in HCC. Moreover, SEMA3F was also markedly positively associated with biomarkers of these infiltrated immune cells.…”
Section: Discussionmentioning
confidence: 65%
“…TILs present pre-existing immunity and are useful markers response to immunotherapy in breast cancer, especially for TNBC. 36 , 37 The subgroups of TILs in the tumor microenvironment mainly include CD4 + cell, CD8 + cell, and regulatory T cell. Our results show that the key module was mostly related to activated and memory CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%